(untitled) - Sheldon, Robert (Indianapolis, IN, 2005)
Provides programmers with a complete foundation in MySQL, the multi-user, multi-threaded SQL database server that easily stores, updates, and accesses information
Keywords: SQL (Computer program language),SQL (ngôn ngữ lập trình máy tính)